HEALTH EDUCATION ABOUT BULLYING FOR STUDENTS AT SMPN 3 BANYUMAS - Yunida Triana, Noor; Murniati, Murniati (LPPM Univ. Ibn Khaldun Bogor, 2024)
Bullying in teenagers is not a strange. A report from the Indonesian Child Protection Commission stated that there were 647 incidents of bullying in schools between 2014 and 2016. Bullying creates feelings of depression, physical and psychological pain, loss of self-confidence, fear, trauma, feelings of helplessness and guilt, anxiety to go to school and even suicidal thoughts. One way to prevent bullying incidents is to provide health education. There are various types of health education media such as radio, short visual films, demonstrations, television, graphic videos and print media. One of the popular media is pocket books and leaflets. The purpose of this community service is to provide health education on bullying at SMP N 3 Banyumas to increase adolescents’ awareness and knowledge about bullying. This method of implementing community service is carried out in three stages: the first is the socialization stage for teenagers at school; the second is the implementation of training, namely health education about bullying; and the third application of technology, mentoring and evaluation; and the sustainability of the program. The results of this community service are that there is an increase in students-knowledge about bullying and how to prevent it from before counseling, the level of good knowledge of 16.1% (5 participants) increasing to 51.6% (16 participants). The output this community service are national journals and IPR pocket books which will be used by lecturers for BKD reporting every semester.